2019
DOI: 10.1016/j.fcr.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Farming on the fringe: Shallow groundwater dynamics and irrigation scheduling for maize and wheat in Bangladesh’s coastal delta

Abstract: Highlights Maize and wheat are proposed for diversification, but irrigation advice is limited. Soil moisture content was above or near drained upper limit for depths below 0.5 m. A significant effect of irrigation on yield was observed for maize only, in one year. One irrigation, in addition to a starter irrigation, generally is sufficient to grow a crop. Low-input maize cultivation is not always profitable and low fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…All Rights Reserved.302mm at Rangpur to 360mm at Rajshahi respectively. The results were coincident with Schulthess, et al[14]…”
supporting
confidence: 92%
“…All Rights Reserved.302mm at Rangpur to 360mm at Rajshahi respectively. The results were coincident with Schulthess, et al[14]…”
supporting
confidence: 92%
“…This follows from the fact that at all three sites, the evapotranspiration is less than rainfall and most of the crop needs are supplied by the combined water storage of the soil and shallow groundwater. Schulthess et al 61 also found that irrigation had little impact on maize and no impact on wheat in the same area. The impact was significant only in the driest years of their trials 61 .…”
Section: Discussionmentioning
confidence: 93%
“…Schulthess et al 61 also found that irrigation had little impact on maize and no impact on wheat in the same area. The impact was significant only in the driest years of their trials 61 . However, the polder model is not a detailed crop model and is not responsive to the timing of irrigation events, some of which may be important 31 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It also aims to achieve the strategic goal of shifting boro rice entirely or partially to the southern coasts to offset the increasing energy costs and massive depletion of groundwater as a result of intensive boro production in northern Bangladesh (Qureshi et al, 2015). The feasibility of this approach is questionable, in lieu of the farmers' preferences to abandon agriculture or grow low-yielding but lowinput-dependent pulses in the dry season (Aravindakshan et al, 2020;Schulthess et al, 2019). In addition, the region experiences increasing soil and water salinity as the dry season progresses-a situation exacerbated by water competition as described above-and extreme weather events, and is at risk of climate change-induced sea-level rise (Krupnik et al, 2017;Qureshi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%